The Effect of Psychology Objective Structured Clinical Examination Scenarios Presentation Order on Students Autonomic Stress Response - Bellido-Esteban, Alberto; Beltrán-Velasco, Ana Isabel; Ruisoto-Palomera, Pablo; Nikolaidis, Pantelis T.; Knechtle, Beat; Clemente-Suárez, Vicente Javier (Frontiers in Psychology, 2021)
The objective structured clinical examination (OSCE) is a method for assessment clinical competencies and skills. However, there is a need to improve its design in psychology programs. The aim of this study was to analyze the effect of the different scenario's presentation order with different complexity/difficulty on the autonomic stress response of undergraduate students undergoing a Psychology OSCE. A total of 32 students of Psychology Bachelor's Degree (23.4 ± 2.5 years) were randomly selected and assigned to two OSCE scenarios of different complexity. While undergoing the scenarios, participants heart rate variability was analyzed as an indicator of participant's stress autonomic response. Results indicate that the order of presentation of different complexity/difficulty scenarios affects the autonomic stress response of undergraduate Psychology students undergoing an OSCE. Students who underwent the high-complexity scenario (difficult) first, reported significantly higher autonomic stress response than students who began the OSCE with the low-complexity scenario (easy). Highly complex or difficult scenarios require good executive functions or cognitive control, very sensitive to autonomic stress responses. Therefore, OSCE design will benefit from placing easy scenarios first.